Engaging busy teachers of young learners in in-service English training - Fransisca Endang Lestariningsih; Lemmuela Alvita Kurniawati (Universitas Islam Sultan Agung, 2022)
Highly qualified and competent teachers are the key for outstanding education systems. Teachers, however, are too busy with administrative work. Accordingly conducting engaging in-service training for them is a relief, as well as a way to improve their teaching skills. The aim of this research is to report the in-service English training in a bilingual school in Yogyakarta Special Province, Indonesia, which the outcome is to improve the English skills of the teachers as a means of teaching (EMI – English as a Medium of Instruction). Questionnaires, interviews, and written reflections were the techniques of collecting the data. The result of the training shows that through some light hands-on activities, the teachers’ motivation and engagement improved. This improvement resulted in the increase in using classroom language instructions.